2020
DOI: 10.1111/ajco.13302
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between CD4+FoxP3+ Treg and expression of FoxM1 and Ki‐67 in gastric cancer patients

Abstract: In this study, we intended to analyze the clinical significance of CD4 + FoxP3 + Tregs in gastric cancer patients and investigate the relationship between the proportion of CD4 + FoxP3 + Tregs in the peripheral blood and the expression of FoxM1 and Ki-67 in gastric cancer tissues. Methods: Flow cytometry was used to measure the CD4 + FoxP3 + Tregs level in peripheral blood from 70 gastric cancer patients one day before gastrectomy and D2 lymph node dissection. Immunohistochemistry staining was used to detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The increased number of CD8 + T cells contributed to promoted cell death, restricted inflammatory symptoms, and upgraded cytotoxicity of CCA 42 . Likewise, a previous report indicated that FoxM1 overexpression enhanced the number of CD4 + CD8 + Treg cells and Ki67 protein levels, to strengthen the immune escape of gastric cancer 43 . Our findings indicated that FoxM1 promoted FoxP3 transcription to recruit Treg cells, so as to induce HCCA cell immune escape.…”
Section: Discussionsupporting
confidence: 67%
“…The increased number of CD8 + T cells contributed to promoted cell death, restricted inflammatory symptoms, and upgraded cytotoxicity of CCA 42 . Likewise, a previous report indicated that FoxM1 overexpression enhanced the number of CD4 + CD8 + Treg cells and Ki67 protein levels, to strengthen the immune escape of gastric cancer 43 . Our findings indicated that FoxM1 promoted FoxP3 transcription to recruit Treg cells, so as to induce HCCA cell immune escape.…”
Section: Discussionsupporting
confidence: 67%
“…including hepatocellular carcinoma and gastric cancer [40,41] . Previous study suggested that chromosome containing the PSTPIP1 gene was absent in prostate cancer [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the number of CD4 + FOXP3 + Treg cells is positively correlated with the expression of FOXM-1 and Ki-67, which are related to immunosuppression in GC. 100 The formation of a complex TME, including CD4 + /CD8 + T cells and FOXP3 + Treg cells, ultimately affects the progression and survival of GC. 101 In summary, the IL-33/ST2 signaling pathway triggers mast cells to produce IL-11, which induces the occurrence and development of GC.…”
Section: Gastric Cancermentioning
confidence: 99%